2013
DOI: 10.1155/2013/560632
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Adalimumab in the Treatment of Refractory Uveitis Associated with Juvenile Idiopathic Arthritis

Abstract: Purpose. To assess the efficacy and safety of adalimumab in patients with juvenile idiopathic arthritis (JIA) and associated refractory uveitis. Design. Multicenter, prospective case series. Methods. Thirty-nine patients (mean [SD] age of 11.5 [7.9] years) with JIA-associated uveitis who were either not responsive to standard immunosuppressive therapy or intolerant to it were enrolled. Patients aged 13–17 years were treated with 40 mg of adalimumab every other week for 6 months and those aged 4–12 years receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
0
31
0
6
Order By: Relevance
“…All of them were observational in design (three case series; [106][107][108] one Italian registry-based study; 109 one comparative cohort study 110 ), and all assessed treatment with adalimumab (with one also assessing infliximab 110 in uveitis patient populations with varying proportions of JIA uveitis. We have not performed an independent critical appraisal of these studies in this assessment report.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…All of them were observational in design (three case series; [106][107][108] one Italian registry-based study; 109 one comparative cohort study 110 ), and all assessed treatment with adalimumab (with one also assessing infliximab 110 in uveitis patient populations with varying proportions of JIA uveitis. We have not performed an independent critical appraisal of these studies in this assessment report.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…Steroid sparing effects, found in our patient cohort, enabled reduction and complete ending of steroids after commencing adalimumab and methotrexate, which is in concordance with published data. 38,39 The fact that no serious adverse events were recorded during the followup period indicates that safety profile of these therapeutic options is high. Patients only reported pain at the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…It is administered via subcutaneous injection by the patient. Noncontrolled case series have suggested that adalimumab is effective and well-tolerated in patients with JIA and Behçet'sassociated uveitis [89,90]. Adalimumab is initially dosed at 40 mg subcutaneously every 2 weeks.…”
Section: Adalimumabmentioning
confidence: 99%